2018
DOI: 10.1093/biosci/bix149
|View full text |Cite
|
Sign up to set email alerts
|

Urban Mind: Using Smartphone Technologies to Investigate the Impact of Nature on Mental Well-Being in Real Time

Abstract: Existing evidence on the beneficial effects of nature on mental health comes from studies using cross-sectional designs. We developed a smartphone-based tool (Urban Mind; www.urbanmind.info) to examine how exposure to natural features within the built environment affects mental well-being in real time. The tool was used to monitor 108 individuals who completed 3013 assessments over a 1-week period. Significant immediate and lagged associations with mental well-being were found for several natural features. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
1
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 48 publications
6
78
1
6
Order By: Relevance
“…This does not take into account the diversity of effects that plants have on other organisms, for instance as interaction partners in mutualistic relationships, as habitat, or even for ecosystem services, e.g. related to tourism (Grünewald et al 2016, Arbieu et al 2017 or human well-being (Lindemann-Matthies et al 2010, Bakolis et al 2018). The framework introduced in this article offers a methodological base for these new kinds of analyses that complement the existingalready very advanced -fields of FD research.…”
Section: Discussionmentioning
confidence: 99%
“…This does not take into account the diversity of effects that plants have on other organisms, for instance as interaction partners in mutualistic relationships, as habitat, or even for ecosystem services, e.g. related to tourism (Grünewald et al 2016, Arbieu et al 2017 or human well-being (Lindemann-Matthies et al 2010, Bakolis et al 2018). The framework introduced in this article offers a methodological base for these new kinds of analyses that complement the existingalready very advanced -fields of FD research.…”
Section: Discussionmentioning
confidence: 99%
“…[17] found that participants were happier outdoors in blue and green areas of all habitat types compared with inland bare ground and continuous urban areas. [18] found greater wellbeing in natural environments, with particular benefit to participants who scored high on trait impulsivity. Despite being happier outdoors, participants only spent 7.48% of their time outdoors each day [17].…”
Section: Current Wellbeing/nature Apps Available and Limitationsmentioning
confidence: 93%
“…To date, there have been two published studies which have used an app to assess the link between green and urban spaces and wellbeing ('Mappiness' [17] & 'Urban Mind' [18]). The Mappiness app sent prompts to participants at random times during the day (participants chose the number of prompts) asking them to self-report their wellbeing whilst tracking their location using GPS.…”
Section: Current Wellbeing/nature Apps Available and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations